Peningkatan Kompetensi Siswa pada Pembelajaran Tematik Menggunakan Pendekatan Steam ”Sanak Sabin” - Rindang Djoko Triasmoro (Jurnal Didaktika Pendidikan Dasar, 2020)
The approach of Science Technology Engineering Arts Mathematics (STEAM) is now widely applied in the learning process in Indonesia. Through this approach, educators and students are expected to be able to have process skills that will deliver them to a certain level of competence. So that they are able to be competitive and efficient in facing the challenges of 21st century life. Sanak Sabon is a program of learning activities carried out at Brenggolo 1 Elementary School in grade 4. Learning innovations using Sabon Sanak are considered capable of providing answers to several problems of daily life that experienced by students, as well as in order to realize the achievement of basic competencies that exist in some learning content. The elements of learning content in Natural Sciences, Pancasila and Citizenship Education, Social Sciences, Indonesian Language, SBDP, and Mathematics are combined in a real work with the name of the program One Child One Doll (Sanak Sabon). Sabon relatives are carried out in several processes that must be passed by students. That's when they learned some important lessons. Through this research, it is known that the achievement of competencies in the basic competencies of lesson content in Theme 3 about caring for living creatures, increased from an average of 73.00% to 89.75%. The learning atmosphere becomes more lively because the Sanak Sabon program is able to increase students' motivation and enthusiasm for learning. Through learning to use Sanak Sabon, students are able to learn about how to overcome social problems, for example about plastic pollution in the surrounding environment.